Peningkatan Perilaku Hidup Bersih Dan Sehat Melalui Edukasi Sampah Rumah Tangga - yuliana, lina; Luqmantoro, Luqmantoro; Zainul, L.M. Zainul; Siboro, Impol; Mulya, Widya; Rizal, Muhammad; Hana Eka; Sipahutar, Merry K; Wahyuni, Sri (Program Studi D4 K3 Universitas Balikpapan, 2022)
The socialization in this service activity aims to: (1) increase public knowledge of the importance of household waste management (2) to grow and increase public awareness and awareness of disposing of waste in its place (3) so that people know about the financial benefits of inorganic waste management which is good and true. The target audience for PPM activities is 60 housewives in RT 35. The PPM activity method uses the question and answer lecture method, and simulation. The steps for PPM activities are lectures to explain the study of waste, types and classification of waste, waste management and 3R (reduce, reuse, recycle) inorganic waste management, and the impact of waste on personal health and the environment. After that, it was followed by a question and answer session and a simulation of the management of inorganic waste into various recycled creations. The supporting factors for the service activities are the support from the village head, the head of the Damai Village LPM, the Representative of the Waste Bank Team from the Environment Agency, the Head of RT 35, the Chair of the PKK Cadre, and the enthusiasm of the service participants, while the inhibiting factor for the activity is the limited time for the implementation of service activities. Overall service activities can be said to be good and successful, seen from the success of the target number of socialization participants (85%), the achievement of training objectives (80%), the achievement of the planned material targets (90%), and the ability of participants in mastering the material (90% ). Service activities can increase the knowledge of housewives about waste management in order to improve clean and healthy living behavior by empowering them in managing inorganic waste into various recycled creations and new sources of income from the sale of waste to the waste bank.